The Impact of Socioeconomic Changes on the Educational Outcomes of Refugee Host Populations - Hailat, Mahmud; Magableh, Sohail (Migration Letters, 2023)
The study aims to investigate the impact of household socio-economic conditions on school attendance, enrolment in the university, and years of schooling before and after the influx of refugees in Jordan. The study deploys a quantitative secondary research design and gathers micro-data from the Jordan Labour Market Panel survey of 2010 and 2016. The results of the study show that household socioeconomic conditions particularly household wealth and parents’ education impacted the educational outcomes. Between 2010 and 2016, the total enrolment in education declined by 5.4%, school attendance dropped from 92.4% to 88.3% whereas the enrolment rate in university education also decreased by 5% in the same period. Lastly, the study found regional disparities whereas no evidence that Jordanians who were living in the refugee host governorates were disadvantaged in terms of neither enrolment nor years of schooling which shows that there was no direct influence of the influx of refugees on the educational outcomes of the host population. To lessen negative consequences and maintain the host population’s support for the presence of refugees, policy mediation may be required. When conditions are ideal, hosting refugees may encourage regional economic growth that will benefit both locals and refugees.